Population Pharmacokinetics of Ipatasertib and Its Metabolite in Cancer Patients. (11th August 2021) - Yoshida, Kenta; Wilkins, Justin; Winkler, Julia; Wade, Janet R.; Kotani, Naoki; Wang, Nina; Sane, Rucha; Chanu, Pascal
Abstract: Ipatasertib is a selective AKT kinase inhibitor currently in development for the treatment of several solid tumors, including breast and prostate cancers. This study was undertaken to characterize pharmacokinetic profiles of ipatasertib and its metabolite M1 (G‐037720) and to understand the sources of variability. Population pharmacokinetic models of ipatasertib and M1 were developed separately using data from 342 individuals with cancer from 5 phase 1 and 2 studies. The final population pharmacokinetic models for ipatasertib and M1 were 3‐compartmental, with first‐order elimination and sequential zero‐ and first‐order absorption. Ipatasertib bioavailability and M1 formation increased after multiple dosing, resulting in an increase in exposure beyond that expected from accumulation alone. Covariate effects of ipatasertib include decreased oral clearance with increasing age and with coadministration of abiraterone, as well as decreased bioavailability with increasing weight. For ages 37 and 80 years, steady‐state area under the curve (AUCss ) was predicted to be 81% and 109%, respectively, of the typical population value (64 years). For body weight of 49 and 111 kg, AUCss was predicted to be 132% and 78%, respectively, of the typical population value (75 kg). The small magnitude of change in ipatasertib exposure is not likely to be clinically relevant. For M1, the peripheral distribution volume and intercompartmental clearance increased with increasing weight. Coadministration of abiraterone was estimated to increase M1 exposure by 61% at steady state. Mild and moderate renal impairment, mild hepatic impairment, and race were not identified as significant covariates in the final models for ipatasertib and M1.